2011
DOI: 10.1100/2011/545421
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities ofGinkgo bilobaL. Leaf Extracts

Abstract: The antibacterial activity of methanol, ethanol, chloroform, and hexane extracts of the leaves of Himalayan gymnospermous plant Ginkgo biloba L. was assessed against five animal and plant pathogenic strains (Agrobacterium tumefaciens, Bacillus subtilis, Escherichia coli, Erwinia chrysanthemi, and Xanthomonas phaseoli) employing disc-diffusion and broth-dilution assays. The methanol extract showed the highest activity (zone of inhibition of 15–21 mm) followed by ethanol (14–19 mm), chloroform (15–20 mm), and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…All the wells showing no visible growth of strains were subcultured and incubated at 37 °C ( Salmonella enterica , Staphylocococus aureus ) and 28 °C ( Aspergillus niger ) overnight. The highest dilution showing 100% inhibition was recorded as MBC or MFC [12]. The FIC is the concentration that kills when used in combination with another agent divided by the concentration that has the same effect when used alone [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the wells showing no visible growth of strains were subcultured and incubated at 37 °C ( Salmonella enterica , Staphylocococus aureus ) and 28 °C ( Aspergillus niger ) overnight. The highest dilution showing 100% inhibition was recorded as MBC or MFC [12]. The FIC is the concentration that kills when used in combination with another agent divided by the concentration that has the same effect when used alone [33].…”
Section: Methodsmentioning
confidence: 99%
“…Sati et al reported that hexane extracts of GBL showed actovoty against five pathogenic strains [12]. A chloroform fraction prepared from the sarcotesta of GBL where the active compounds were identified as salicylic acids showed potent inhibitory activity against vancomycin-resistant Enterococcus (VRE) [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that modern nonangiospermous plants are significantly affected by plant diseases, frequently identifiable by a variety of externally evident signs (Sinclair et al, 1987;Johnson and Lyon, 1991). With the exception of certain conifer taxa, most of these lineages are of minimal economic value, although other taxa such as lycopod species of Huperzia, bracken, certain cycads, Ginkgo biloba, and the gnetalean Ephedra have been used extensively as ornamentals in horticulture, as well as in herbal remedies for human ailments and diseases (Wu et al, 1995;Ling et al, 1995;Sati and Joshi, 2011), and have yielded extracts used in agriculture and the pharmaceutical industry (Young et al, 1997;Read et al, 2000;Roy et al, 2000;Saxena and Harinder, 2004;Womack and Burge, 2006).…”
Section: Can Plant Diseases Be Recognized In the Preangiospermous Fosmentioning
confidence: 99%
“…Extracts of G. biloba leaves have been found to possess anti-diabetic, antiasthmatic, antimicro bi al, cardioprotective, hepatoprotective and potent central nervous system activities (Pietri et al, 1997;Mazzanti et al, 2000;Naik and Panda, 2007;Panda and Naik, 2008;Sati and Joshi, 2011). G. biloba contains numerous therapeutically active phyto-constituents such as flavonoids, diterpenes and sesquiterpene lactones which have shown potent scavenging activities (Braquet, 1987;Kleijnen and Knipschild, 1992;Naik et al, 2006;Kaur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%